Case Report: A rare case of bilateral primary Müllerian adenosarcoma of the ovary with Uncommon extensive metastasis and GNAQ mutation - Ai, Shuying; Li, Simin; He, Huihua; Yuan, Jingping; Yan, Honglin; Zhang, Xiuyun (Frontiers in Oncology, 2025)
BackgroundMüllerian adenosarcoma (MA) is a rare low-grade malignant tumor. It is characterized by benign glandular epithelium and malignant sarcomatous stromal components. This tumor commonly arises in the uterine corpus. Primary ovarian MA is uncommon and typically presents as a unilateral lesion (FIGO stages I-III). However, bilateral ovarian involvement coupled with extensive metastasis in ovarian adenosarcoma has not been previously reported.Case presentationThis article reports a rare case of bilateral primary ovarian adenosarcoma with extensive metastasis and lymphovascular invasion (LVI). Histopathological examination revealed a biphasic tumor composed of proliferative glands and stroma. The glandular epithelium was separated by abundant stromal components, forming a lobulated architecture resembling a breast phyllodes tumor. The glandular epithelial cells exhibited a single-layered columnar morphology with bland cytological features. In contrast, the stromal cells displayed a spindle-shaped morphology, arranged densely around spiral artery-like vessels. These stromal cells showed mild atypia with visible mitotic figures. Notably, periglandular stromal condensation formed a characteristic “cuff-like” pattern. Extensive metastases were identified in multiple sites: the subumbilical region, intestinal tract, omentum, and distal segment of the right ureter. Significantly, tumor emboli were detected within vascular channels beneath the rectal serosa. Molecular analysis revealed novel findings. Next-generation sequencing (NGS) identified a GNAQ mutation, previously unreported in this tumor type. Additionally, immunohistochemical (IHC) analysis confirmed positive PD-L1 expression. Finally, the patient received a comprehensive treatment regimen comprising radiotherapy, chemotherapy, and immunotherapy.ConclusionWe describe a unique case of ovarian adenosarcoma presenting with bilateral ovarian involvement, manifesting at the more advanced stage IIIC, notably in the absence of sarcomatous overgrowth (SO). Moreover, we report for the first time the presence of LVI and the GNAQ missense variant in ovarian adenosarcoma.